use of UHMWPE chips to obtain blends with high density polyethylenes - González, Jeanette; Rosales, Carmen; León, Natalia; González, Marco; Rojas, Héctor; Silva, María Gabriela (Rev. Téc. Fac. Ing. Univ. Zulia, 2017)
The accumulation of shavings of ultra-high molecular weight polyethylene (UHMWPE), a product used for manufacturing machine elements, creates serious problems in production plants. In order to promote a possible reuse of this waste and thus reduce the environmental impact they generate, blends with UHMWPE and two different grades of high density polyethylene (HDPE) were prepared in a twin-screw extruder and followed by compression molding. Rheological and mechanical (tensile and abrasion) properties for the blends prepared were evaluated, and its morphology using scanning electron microscopy was observed. Results showed that all HDPE blends exhibited an increase in abrasion resistance, little variations in tensile properties and an increase in complex viscosity and storage and loss modulus when the UHMWPE proportion increases. It should also be noted that the new material (HDPE, injection molding grade/UHMWPE, 80/20) may replace the HDPE, blow molding grade in similar applications because both materials have similar tensile properties and rheological behavior.